2013 IEEE 13th International Conference on Rehabilitation Robotics (ICORR) 2013
DOI: 10.1109/icorr.2013.6650461
|View full text |Cite
|
Sign up to set email alerts
|

Effort, performance, and motivation: Insights from robot-assisted training of human golf putting and rat grip strength

Abstract: Robotic devices can modulate success rates and required effort levels during motor training, but it is unclear how this affects performance gains and motivation. Here we present results from training unimpaired humans in a virtual golf-putting task, and training spinal cord injured (SCI) rats in a grip strength task using robotically modulated success rates and effort levels. Robotic assistance in golf practice increased trainees feelings of competence, and, paradoxically, increased their sense effort, even th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Further, none of these four participants improved their performance from day 1 to day 2 of therapy, which could have reduced their motivation to continue. This is in line with other studies that have shown high levels of difficulty or lack of improvement in a task can reduce motivation to persist [57][58][59]. Based on the results of this study, a minimum average performance of 20 percent in the MusicGlove game may be an important factor for maintaining motivation during home therapy with the device.…”
Section: Influence Of Motivating Factors On Dose Of Exercise and Longsupporting
confidence: 77%
“…Further, none of these four participants improved their performance from day 1 to day 2 of therapy, which could have reduced their motivation to continue. This is in line with other studies that have shown high levels of difficulty or lack of improvement in a task can reduce motivation to persist [57][58][59]. Based on the results of this study, a minimum average performance of 20 percent in the MusicGlove game may be an important factor for maintaining motivation during home therapy with the device.…”
Section: Influence Of Motivating Factors On Dose Of Exercise and Longsupporting
confidence: 77%
“…Although there was no increase in BPF with repetitive training after the cervical SCI on a group level, the percentage of strength recovery, relative to the pre-lesion abilities of each rat, significantly increased in the group that experienced adaptive strength training that challenged them each training day. [11][12][13] If training with RUE can increase forelimb force production, the device may be useful for enhancing neuroplasticity and neuroregeneration in rehabilitation treatments 22,23 The training paradigm presented can readily be used in the treatment of other neurological injuries, such as more severe SCI, and brain injury, such as stroke; RUE is currently being used by other research groups to study the motor effects and rehabilitation of these types of injuries.…”
Section: Rue As a Rehabilitation Toolmentioning
confidence: 99%
“…Briefly, rats were trained with either a constant force-set at a value much lower than their maximum strength-or with an adaptive algorithm that progressively required increasing force production so as to assess maximum strength. [11][12][13] GSM. We followed the procedure previously developed for use with the GSM in SCI models.…”
Section: Measuring Forelimb Force Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…After training, it evaluated the effect of the training, combining the collected motion information with clinical evaluation methods. Reinkensmeyer, et al [7][8][9] developed a rehabilitation training device that could control three degrees of freedom by using a magnetic powder brake and a motor. This device can examine hand movements at different locations, and the rehabilitation effect was analyzed by comparing the actual location and the target location of patient hand movements.…”
Section: Introductionmentioning
confidence: 99%